Awareness of Diabetic Retinopathy among Diabetic Patients - Imran Hassan Khan, Asif Manzoor, Lubna Siddiq Mian, Muhammad Moin (Pakistan Journal of Ophthalmology, 2017)
Objective: To find the impact of disease duration and education on the awareness of diabetic retinopathy among diabetic patients visiting a tertiary care hospital in a in a developing country. Study Design: Cross-sectional study. Place and Duration of Study: Lahore General Hospital from 1st January, 2016 to 28th February, 2016. Materials and Methods: An interviewer administered questionnaire was used to assess patients’ awareness about ocular complications of diabetes on a 9-point questionnaire before their fundus examination using non-mydriatic fundus camera in the eye clinic. The questions were designed to observe the knowledge and awareness about systemic and ocular complications of diabetes, diabetic retinopathy, the availability of its treatment, treatment modalities, disease consequences and its preventive measures. The patients were divided into 2 groups A and B according to their educational levels and 2 groups C and D according to the duration of disease. Results: Among the enrolled 200 patients, 69 (34.5%) were male and 131 (65.5%) patients were female. The mean age of the participants was 48 + SD 10.57 years. Patient’s education affected their knowledge about the normal random blood sugar levels (P = 0.001), the vascular complications of diabetes involving the retina (P = 0.008) and the absence of the role of glasses in treatment (P = 0.014). Duration of diabetes improved patients knowledge about normal random blood sugar levels (P < 0.001), the vascular nature of disease (P < 0.001), its blinding potential (P < 0.001) and its role in early cataract formation (P < 0.001). It also contributed in patients’ motivation to seek annual fundus examination (P = 0.004). Conclusion: The knowledge about diabetic retinopathy and its treatment was poor along with poor compliance with annual fundus examination. This is directly related to the educational level of the patient and the duration of diabetes. Key Words: Diabetic retinopathy, awareness, annual fundus examination, screening, laser, intraocular injections.